2021
DOI: 10.3389/fphar.2020.612573
|View full text |Cite
|
Sign up to set email alerts
|

miRNome profiling of LSC-enriched CD34+CD38−CD26+ fraction in Ph+ CML-CP samples from Argentinean patients: a potential new pharmacogenomic tool

Abstract: Chronic myeloid leukemia (CML) is a myeloid stem cell neoplasm characterized by an expansion of myeloid progenitor cells and the presence of BCR-ABL1 oncoprotein. Since the introduction of specific BCR-ABL1 tyrosine kinase inhibitors (TKI), overall survival has improved significantly. However, under long-term therapy patients may have residual disease that originates from TKI-resistant leukemic stem cells (LSC). In this work, we analyzed the miRNome of LSC-enriched CD34+CD38−CD26+ and normal hematopoietic stem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Targeting IL1RAP by antibodies and novel CAR Tcell therapy has been found to exert anti-leukemic effects in vivo and in vitro through specific killing, with no severe negative effects on normal HSC (159,160). CD26 (DPPV) has also proved to be a novel, specific biomarker for CML LSCs, which is promising for the diagnosis and targeted treatment of CML (161)(162)(163). In a recent study, a venetoclax-loaded immunoliposome remarkably induced apoptosis in CD26+ cells in both stem cells and progenitor cells population (164).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…Targeting IL1RAP by antibodies and novel CAR Tcell therapy has been found to exert anti-leukemic effects in vivo and in vitro through specific killing, with no severe negative effects on normal HSC (159,160). CD26 (DPPV) has also proved to be a novel, specific biomarker for CML LSCs, which is promising for the diagnosis and targeted treatment of CML (161)(162)(163). In a recent study, a venetoclax-loaded immunoliposome remarkably induced apoptosis in CD26+ cells in both stem cells and progenitor cells population (164).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…Moreover, recent data revealed that miR-300 is a tumor suppressor miRNA inducing quiescence in CML leukemic stem cells (LSCs) [141], and that miR-126-3p influences both quiescence and self-renewal of CML LSCs [142] (Table 2). Another recent study showed a global decrease in microRNA levels in LSC-enriched CD34 + CD38 − CD26 + and HSC from CML-CP patients compared to those from healthy donors HSC [143]. Previous findings showed that microRNAs have also been implicated in CML progression, response to treatment, or TKI resistance [144][145][146][147][148][149][150].…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 97%
“…The study revealed that in both CML LSCs CD26+ and CD26− several miRNAs were down-regulated; only the expression of miR-196a-5p was documented in LSCs CD26+ at diagnosis with levels nine-fold more than LSCs CD26−. Additionally, miRNAs were involved in the metabolism of LSCs [ 62 ].…”
Section: Cd26+ Lscs Novel Approach and Therapeutic Rolementioning
confidence: 99%